Models of Policy and Strategic Planning in Strengthening Islamic Education - Aldi, Muhammad; Baharuddin, Baharuddin; Khairanis, Retisfa (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
Education is the main instrument in producing quality human resources, while policy and strategic planning serve as a guiding framework in achieving national education goals. In the context of Islamic Religious Education (IRE), education policy not only concerns administrative aspects, but also touches on moral, spiritual, and social dimensions that shape the character of students. This study aims to analyze models of education policy and strategic planning oriented towards strengthening PAI in Indonesia. The research method used is descriptive qualitative study through analysis of literature and national education policy documents, linked to their implementation in the context of Islamic education. The results of the study show that there are three main models in education policy, namely rational, incremental, and participatory models, each of which has an important role in shaping policy directions and implementation strategies in Islamic educational institutions. The integration of these three models can create policies that are adaptive, equitable, and relevant to the needs of the times. The implications of this research emphasize that strengthening PAI requires synergy between strategic planning based on Islamic values and educational governance that is responsive to social, cultural, and globalization dynamics, so that Islamic education can continue to transform into a superior and sustainable system.